DIRECTIONS FOR IMPROVING THE ASSESSMENT OF THE USE OF PAYABLES AND RECEIVABLES - LIKHONOSOVA, Ganna; STAVTSEVA, Elizaveta (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article discusses modern approaches to the assessment of payables and receivables of enterprises in order to increase the efficiency of financial resources management. The main attention is paid to the analysis of problems and shortcomings of existing assessment methods, as well as to the development of new approaches and recommendations for their improvement. The essence and role of payables and receivables in the financial activity of the enterprise is revealed. The main types of debts and their impact on the liquidity and financial stability of the enterprise are described. Traditional methods of assessing payables and receivables, including coefficient and comparative methods, are analyzed. Disadvantages and limitations of the existing approaches were identified, in particular, insufficient flexibility and limited ability to adapt to the specific conditions of the enterprise. New approaches to assessment are proposed, including the use of modern information technologies and automated management systems. The need to integrate risk analysis and cash flow forecasting into the debt assessment process is substantiated. Recommendations for the implementation of new methods of assessing payables and receivables have been developed. The advantages of using integrated approaches and their impact on increasing the financial stability of the enterprise are described. The main results of the research are summarized and the directions of further scientific developments in the field of financial management are determined. The article provides a comprehensive analysis of existing approaches to the assessment of payables and receivables, identifies their main shortcomings, and suggests ways to eliminate them. The developed recommendations will contribute to improving the management of financial resources of enterprises, increasing their liquidity and financial stability. Further research should be aimed at the practical implementation of the proposed approaches and their adaptation to various branches of the economy.